Investigation of antiparkinsonian activity of new imidazole-4,5-dicarboxylic acid derivatives on the experimental model of catalepsy - Vladimir D. Dergachev; Ekaterina E. Yakovleva; Maria A. Brusina; Evgeny R. Bychkov; Levon B. Piotrovskiy; Petr D. Shabanov (Belgorod National Research University, 2023)
Introduction: To study the antiparkinsonian activity of new ligands of the glutamate NMDA receptor complex - 1,2-substituted imidazole-4,5-dicarboxylic acids - on an experimental model of catalepsy caused by haloperidolintraabdominal injections in rats. Materials and methods: The experiments were performed on Wistar rats weighing 300-350 g, obtained from the Rappolovo nursery of the Russian Academy of Medical Sciences (Leningrad Region). The animals were kept in standard plastic cages in vivarium conditions with free access to water and food at a temperature of 22±2 °C and in the experiment were divided into several groups (6 animals each). All the experiments were carried out in the autumn-winter period. The animals were kept in accordance with the rules of laboratory practice (GLP), regulatory documents "Sanitary Rules for the Device, Equipment and Maintenance of Vivarium" and the Order of the Ministry of Health and Social Development of the Russian Federation dated 23.08.2010 No. 708n "On Approval of the Rules of Laboratory Practice". Imidazole-dicarboxylic acid derivatives (IEM-2295, IEM-2296) were injected intraperitoneally at doses from 5 mg/kg to 40 mg/kg simultaneously with haloperidol at a dose of 1 mg/kg, after which the duration and severity of catalepsy were evaluated after 30, 60, 120 minutes from 0 to 6 points according to the Morpurgo method. Results: The severity of catalepsy with the injection of IEM-2295 decreased on average to 3 points, while in the control group it remained at the level of 6 points throughout the observation. However, the severity of catalepsy with the introduction of IEM-2296 decreased to an average of 4 points, but the effect itself lasted longer than with the introduction of IEM-2295. Thus, it was noted that by the 120th minute of observation, the severity of catalepsy in rats receiving the IEM-2295 compound averaged 5 points, whereas in animals receiving IEM-2296 - 3 points. Discussion: Basing on the results of our work and similar experiments, we can conclude that the studied compounds, which are not channel blockers, have an active effect on dopaminergic neurotransmission, because of which the symptoms of catalepsy that occur when haloperidol is injected to rats were stopped to one degree or another. Conclusion: The studied substances exhibit antiparkinsonian activity on an experimental haloperidol model of catalepsy in rats and are promising for development as potential therapies for neurodegenerative diseases. Further study of these compounds and other ligands from the NMDA-blocker group in a wider sample on the catalepsy model, as well as on other models of Parkinsonism, is required.